The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1161/jaha.114.000946
|View full text |Cite
|
Sign up to set email alerts
|

Single Intracoronary Injection of Encapsulated Antagomir‐92a Promotes Angiogenesis and Prevents Adverse Infarct Remodeling

Abstract: BackgroundSmall and large preclinical animal models have shown that antagomir‐92a‐based therapy reduces early postischemic loss of function, but its effect on postinfarction remodeling is not known. In addition, the reported remote miR‐92a inhibition in noncardiac organs prevents the translation of nonvectorized miR‐targeted therapy to the clinical setting. We investigated whether a single intracoronary administration of antagomir‐92a encapsulated in microspheres could prevent deleterious remodeling of myocard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(44 citation statements)
references
References 53 publications
1
42
0
1
Order By: Relevance
“…Bellera et al . demonstrated that a single intracoronary administration of antagomiR‐92a encapsulated in specific microspheres inhibited miR‐92a, resulting in significant vessel growth in a local, selective and sustained manner in a pig model of AMI. Bonauer et al .…”
Section: Ncrnas Modulate Angiogenesis In Ischaemic Areasmentioning
confidence: 99%
“…Bellera et al . demonstrated that a single intracoronary administration of antagomiR‐92a encapsulated in specific microspheres inhibited miR‐92a, resulting in significant vessel growth in a local, selective and sustained manner in a pig model of AMI. Bonauer et al .…”
Section: Ncrnas Modulate Angiogenesis In Ischaemic Areasmentioning
confidence: 99%
“…Inhibition of miR-92a increased angiogenesis in vivo and improved blood flow recovery after hindlimb ischemia [42]. Furthermore, administration of miR-92a inhibitors in porcine models for myocardial infarction demonstrated that miR-92 inhibition prevents adverse infarct remodeling and ischemia/reperfusion injury [43,44]. Phase 1 trials aimed to improve wound healing with a future potential clinical application towards heart failure treatment have recently been completed for miR-92a inhibitor MRG 110 (NCT03603431) [45].…”
Section: Micrornasmentioning
confidence: 99%
“…Intracoronary administration of antagomiR-92a encapsulated in specific microspheres (9 μm poly-d,-lactide-co-glycolide) was shown to preferentially target the vasculature and augment cardiac function in pigs. 10 But specific strategies for enriched delivery of ASO to the cardiovascular system are sparse. In contrast, for targeting the liver, nanoparticle containing ionizable amino lipids have become the leading delivery technology for siRNA, with several products in clinical trials.…”
Section: Improvement Of the Efficiency And Specificity Of Anti-mirsmentioning
confidence: 99%